Assessing soil erosion and control factors by radiometric technique in the source region of the Yellow River, Tibetan Plateau. Issue 3 (May 2014) - Wang, Yibo; Niu, Fujun; Wu, Qingbai; Gao, Zeyong
Abstract: Measurements of 137 Cs concentration in soils were made in a representative catchment to quantify erosion rates and identify the main factors involved in the erosion in the source region of the Yellow River in the Tibetan Plateau. In order to estimate erosion rates in terms of the main factors affecting soil loss, samples were collected taking into account the slope and vegetation cover along six selected transects within the Dari County catchment. The reference inventory for the area was established at a stable, well-preserved, site of small thickness (value of 2324 Bq·m − 2 ). All the sampling sites had been eroded and 137 Cs inventories varied widely in the topsoil (14.87–25.56 Bq·kg − 1 ). The effective soil loss values were also highly variable (11.03–28.35 t·km − 1 ·yr − 1 ) in line with the vegetation cover change. The radiometric approach was useful in quantifying soil erosion rates and examining patterns of soil movement.